U.S. Hispanic Theology - Bañuelas, Arturo (1992)
A new theological voice is growing increasingly more articulate in the United States—the voice of U.S. Hispanic theologians. In this article Arturo Bañuelas surveys the work of seven major U.S. Hispanic thinkers, sets forth twelve characteristics that are common to this emerging theology, and presents six points of assessment. Even though it is in its nascent stages, Hispanic theology is being done with maturity and depth, and with a sense of urgency arising out of U.S. Hispanics' experience of suffering and marginalization.